The Formation of Fruit Quality in Cucumis sativus L. - Zhang, Juping; Feng, Shengjun; Yuan, Jing; Wang, Chen; Lu, Tao; Wang, Huasen; Yu, Chao (Frontiers in Plant Science, 2021)
Cucumber is one of the most widely grown vegetables in China and an indispensable fresh fruit in the diet. With the development of society, the demand of people for cucumber quality is higher and higher. Therefore, cultivating high-quality cucumber varieties is one of the main goals of cucumber breeding. With the rapid development of biotechnology such as molecular marker, cucumber quality control network is becoming clear. In this review, we describe the formation mechanism of cucumber fruit quality from three aspects: (1) the commercial quality of cucumber fruit, (2) nutritional quality formation, and (3) flavor quality of cucumber fruit. In addition, the determinants of cucumber fruit quality were summarized from two aspects of genetic regulation and cultivation methods in order to provide ideas for cucumber researchers and cultivators to improve fruit quality.